2012
DOI: 10.1111/j.1365-2621.2012.03213.x
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration due to delayed icing and its impacts on the nutritional quality of Malabar travally (Carangoides malabaricus)

Abstract: Summary Effect of delayed icing of the fish Carangoides malabaricus was assessed using chemical and microbial methods to determine the impacts on the nutritional quality and sensory changes. The shelf life of the fishes iced immediately after harvest had a shelf life of 18 days, whereas the delay of icing for 4, 6, 8 and 10 h shortened the shelf life to 14, 10, 6 and 3 days respectively. The spoilage indicators, such as trimethylamine nitrogen, Total volatile basic nitrogen, free fatty acids, peroxide value, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Jeyasanta et al . () showed, e.g., that delaying the icing for 4, 6, 8 or 10 h shortened the shelf life of Malabar trevally ( Carangoides malabaricus ) to 14, 10, 6 and 3 days, respectively, compared with a shelf life of 18 days with immediate icing. Delaying icing of rainbow trout ( Oncorhynchus mykiss ) for 4 or 8 h after the catch shortened the shelf life from 9–11 to 5–7 and 1–3 days, respectively (Rezaei et al .…”
Section: Temperature‐based Techniquesmentioning
confidence: 99%
“…Jeyasanta et al . () showed, e.g., that delaying the icing for 4, 6, 8 or 10 h shortened the shelf life of Malabar trevally ( Carangoides malabaricus ) to 14, 10, 6 and 3 days, respectively, compared with a shelf life of 18 days with immediate icing. Delaying icing of rainbow trout ( Oncorhynchus mykiss ) for 4 or 8 h after the catch shortened the shelf life from 9–11 to 5–7 and 1–3 days, respectively (Rezaei et al .…”
Section: Temperature‐based Techniquesmentioning
confidence: 99%
“…The consistency in the preference value indicates that powdered SFE at all interval storage treatments were acceptable which might be correlated with their biochemical stability. A similar study of the organoleptic test by Jeyasanta et al [17] reported that powdered fish stored at room temperature had acceptable values of appearance, aroma, color, texture, and taste even after storing for up to five months. Furthermore, the low moisture of powdered fish was in the range of 3.28 and 6.5% hence, microbial activities were limited.…”
Section: Resultsmentioning
confidence: 73%
“…After the fish has been killed, begin cooling as quickly as possible. For example, Jeyasanta et al (2013) found that postponing icing for 4, 6, 8, or 10 hours reduced the storage life of Malabar trevally to 14, 10, 6, and 3 days, correspondingly, compared to an 18-day shelf life when the icing was done immediately. The shelf life of rainbow trout (Oncorhynchus mykiss) was reduced from 9-11 to 5-7 and 1-3 days, respectively, by delaying icing by 4 or 8 hours after capture.…”
Section: Coolingmentioning
confidence: 99%